2013
DOI: 10.1055/s-0032-1328187
|View full text |Cite
|
Sign up to set email alerts
|

Botanical Modulation of Menopausal Symptoms: Mechanisms of Action?

Abstract: Menopausal women suffer from a variety of symptoms, including hot flashes and night sweats which can affect quality of life. Although hormone therapy (HT) has been the treatment of choice for relieving these symptoms, HT has been associated with increased breast cancer risk leading many women to search for natural, efficacious, and safe alternatives such as botanical supplements. Data from clinical trials suggesting that botanicals have efficacy for menopausal symptom relief, have been controversial and severa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
82
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(85 citation statements)
references
References 184 publications
(238 reference statements)
1
82
0
2
Order By: Relevance
“…Understanding its molecular mechanism(s) of action is, however, a conditio sine qua non for considering potential beneficial and unwanted side effects. The initially suggested estrogenic activity of lipophilic components, such as triterpenoids, was disproved by later studies (Gaube et al, 2007;Mercado-Feliciano et al, 2012;Hajirahimkhan et al, 2013). There, however, is evidence that A. racemosa L. preparations interact with distinct neurotransmitter systems in the central nervous system, including m-opioid receptors (Rhyu et al, 2006;Reame et al, 2008), serotonin (5-HT) receptors (subtypes 5-HT 1A , 5-HT 1D , and 5-HT 7 ) (Burdette et al, 2003), and dopamine subtype 2 receptors (Jarry et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Understanding its molecular mechanism(s) of action is, however, a conditio sine qua non for considering potential beneficial and unwanted side effects. The initially suggested estrogenic activity of lipophilic components, such as triterpenoids, was disproved by later studies (Gaube et al, 2007;Mercado-Feliciano et al, 2012;Hajirahimkhan et al, 2013). There, however, is evidence that A. racemosa L. preparations interact with distinct neurotransmitter systems in the central nervous system, including m-opioid receptors (Rhyu et al, 2006;Reame et al, 2008), serotonin (5-HT) receptors (subtypes 5-HT 1A , 5-HT 1D , and 5-HT 7 ) (Burdette et al, 2003), and dopamine subtype 2 receptors (Jarry et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…It is agreed that black cohosh is not estrogenic and its mechanism of action may involve modulation of the serotonergic system in a similar manner than antidepressants [1]. This botanical product has been tested in several trials given contradictory results.…”
Section: Clinical Studiesmentioning
confidence: 99%
“…Ohwi (Fabaceae) is a traditional Chinese medicine for the treatment of the symptoms of menopause [1]; the major isolavone in kudzu is puerarin, which is metabolized to daidzein by gut microbiota. Clinical trials with kudzu reported no signiicant changes in the menopausal complaints compared with control group [53].…”
Section: Clinical Studiesmentioning
confidence: 99%
See 2 more Smart Citations